2021
DOI: 10.2147/ndt.s311949
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes among Frontline Health-Care Workers at Eka Kotebe National COVID-19 Treatment Center, Addis Ababa, Ethiopia, 2020: A Cross-Sectional Study

Abstract: Background The COVID-19 pandemic has resulted in many frontline health-care workers vulnerable to developing various mental health conditions. This study aimed to determine prevalence and associated factors of such conditions among frontline workers at Eka Kotebe National COVID-19 Treatment Center in Addis Ababa, Ethiopia. Methods This institution-based cross-sectional study was conducted between May and June 2020 on 280 frontline workers. Mental health outcomes (depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
3
3
1
Order By: Relevance
“…The study found that the odds of having DD are 7.78 times higher among those HCWs who were single as compared to those who were divorced. This result was in line with previous results from Eka kotebe hospital (29), Dessie comprehensive specialized hospital (30), and southern Ethiopia (22). Being single was the psychosocial risk factors of depressive symptoms due to a lack of a partner to express their daily stressors, thereby lacking social support.…”
Section: Discussionsupporting
confidence: 93%
“…The study found that the odds of having DD are 7.78 times higher among those HCWs who were single as compared to those who were divorced. This result was in line with previous results from Eka kotebe hospital (29), Dessie comprehensive specialized hospital (30), and southern Ethiopia (22). Being single was the psychosocial risk factors of depressive symptoms due to a lack of a partner to express their daily stressors, thereby lacking social support.…”
Section: Discussionsupporting
confidence: 93%
“…20,35,36 Previous viral outbreaks showed HCWs at increased risk of psychological adverse effects [36][37][38][39] during and after the epidemics and, also in the framework of COVID-19 outbreak, HCWs were shown to be at increased risk of negative mental health outcomes, among which PTSD. [40][41][42][43][44][45][46] Our finding supports the evidence of previous studies revealing higher levels of functioning impairment among individuals with post-traumatic stress symptoms with respect to those without, with these latter found as predictive factors of impairment in each domain of functioning analyzed in a sample of HCWs facing the COVID-19 pandemic. 35 The present study has some limitations to note.…”
supporting
confidence: 89%
“…In this systematic review and meta-analysis, we included 13 cross sectional studies 8–15 25–29 focused on the impact of COVID-19 on anxiety and stress status among healthcare professionals during COVID-19 in Ethiopia. When we observe the regional distribution, four studies 9 12 15 27 were from SNNP, three studies 11 13 26 were from Oromiya, three studies 8 10 14 were from Amhara, one study 28 was from Addis Ababa and Oromiya, one study 29 was from Addis Ababa and one study 25 was in all regions (national level). Depending on the types of mental disorders, eight studies 8–10 12 25 26 28 29 were reported about anxiety and nine studies 9–11 13–15 26–28 were reported about stress.…”
Section: Resultsmentioning
confidence: 99%